2016
DOI: 10.1021/acs.jafc.5b05904
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Application of BiLA, a Psychrophilic α-Amylase from Bifidobacterium longum

Abstract: In this study, a novel α-amylase was cloned from Bifidobacterium longum and named BiLA. The enzyme exhibited optimal activity at 20 °C and a pH value of 5.0. Kinetic analysis using various carbohydrate substrates revealed that BiLA had the highest k(cat/)K(m) value for amylose. Interestingly, analysis of the enzymatic reaction products demonstrated that BiLA specifically catalyzed the hydrolysis of oligosaccharides and starches up to G5 from the nonreducing ends. To determine whether BiLA can be used to genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 54 publications
3
5
0
Order By: Relevance
“…In general, the measured kinetic parameters were consistent with prior values observed for bacterial enzymes that process these substrates (glycogen 38,39,40 , amylose 41,42 , pullulan 43,41 ). Comparing the specificity constants ( k cat /K m ) for each substrate revealed that glycogen is the preferred substrate for the G. vaginalis and L. iners PulA enzymes.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…In general, the measured kinetic parameters were consistent with prior values observed for bacterial enzymes that process these substrates (glycogen 38,39,40 , amylose 41,42 , pullulan 43,41 ). Comparing the specificity constants ( k cat /K m ) for each substrate revealed that glycogen is the preferred substrate for the G. vaginalis and L. iners PulA enzymes.…”
Section: Resultssupporting
confidence: 87%
“…In general, the measured kinetic parameters were consistent with prior values observed for bacterial enzymes that process these substrates (glycogen 38,39,40 , amylose 41,42 , pullulan 43,41 ).…”
Section: Kinetic Characterization Reveals Different Glycosidic Linkag...supporting
confidence: 86%
“…6 The purified enzyme was analyzed using sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) and stained with Coomassie Brilliant Blue R-250 (Sigma-Aldrich Co.; destaining solution was composed of 20% methanol, 10% (v/v) acetic acid, and water). 18 Enzyme Assay. The hydrolysis enzyme reaction was performed at 45 °C in sodium acetate buffer (50 mM, pH 6.0) containing 0.5% (w/ v) soluble starch, and the hydrolytic activity of CGTase was measured with the 3,5-dinitrosalicylic acid (DNS) method using 1% (w/v) β-CD as a substrate.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The supernatant was purified using a β-CD affinity column with washing (50 mM sodium acetate buffer, pH 6.0) and elution (50 mM sodium acetate buffer (pH 6.0), and 1% (w/v) β-CD) buffers. , The purified enzymes were concentrated using a Centricon filter (Millipore, Bedford, MA, USA) with 50 mM sodium acetate buffer (pH 6.0) . The purified enzyme was analyzed using sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) and stained with Coomassie Brilliant Blue R-250 (Sigma-Aldrich Co.; destaining solution was composed of 20% methanol, 10% (v/v) acetic acid, and water) …”
Section: Methodsmentioning
confidence: 99%
“…The side chain length distribution of starch samples was determined using a method that we described previously [31]. Before the analysis, the sample was pretreated to facilitate the structural analysis of the starch.…”
Section: Side Chain Length Distribution Analysismentioning
confidence: 99%